2020
DOI: 10.3390/atmos11121271
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Ozone Pollution Waves in Central and South Europe—Characteristics, Weather Types, and Association with Mortality

Abstract: Air pollution and hot temperatures present two major health risks, especially for vulnerable groups such as children, the elderly, and people with pre-existing conditions. Episodes of high ozone concentrations and heat waves have been registered throughout Europe and are expected to continue to grow due to climate change. Here, several different heat and ozone wave definitions were applied to characterize the wave-type extremes for two climatically different regions, i.e., Portugal (South Europe) and Bavaria (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 48 publications
0
20
0
1
Order By: Relevance
“…Their relationship and joint occurrences have already presented the focus of a variety of recent health‐related environmental studies (e.g., Abdullah et al., 2017 ; Hertig, 2020 ; Schnell & Prather, 2017 ). There is evidence that the co‐occurrence of both variables results in a human health risk beyond the sum of their individual effects (Hertig et al., 2020 ; Katsouyanni & Analitis, 2009 ; Pattenden et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their relationship and joint occurrences have already presented the focus of a variety of recent health‐related environmental studies (e.g., Abdullah et al., 2017 ; Hertig, 2020 ; Schnell & Prather, 2017 ). There is evidence that the co‐occurrence of both variables results in a human health risk beyond the sum of their individual effects (Hertig et al., 2020 ; Katsouyanni & Analitis, 2009 ; Pattenden et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The general presumption of a strong direct relationship of local ozone and air temperature conditions is further based on the assumption of a high proportion of O 3 in-situ formation by photochemical reactions. If long-range transport processes of ozone from various locations outside the specific o-t-region strongly determine pollution levels, as for example,Hertig et al (2020) found for Portugal, a weaker connection of station-based MDA8O3 levels on local air temperatures can be anticipated. Similar influences and further non-in-situ formation factors might be present in 6-SE with stations spread across Portugal and mainly southern parts of Spain and France.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Adverse effects of low temperatures on overall mortality were, for example, pointed out by Gasparrini et al [43]. Additionally, ozone appears to be of high importance for non-cancer mortality, which is supported by the findings of Hertig et al [62,63]. Still, these findings must be interpreted cautiously, as patient information in the overall mortality dataset is limited.…”
Section: Discussionmentioning
confidence: 85%